Философские проблемы внедрения виртуальной реальности в современное общество - Кутя, Е. Ю. (ХНУРЭ, 2012)
This article opens the questions of modern dinamics of reality virtualization and role of philosophy as a discipline in this process. Also shown positive and negative sides of virtualization and impact which virtualization makes on modern society